Evaluation of "international transfer-out" among foreign-born pulmonary tuberculosis patients in Japan - what are the implications for a cross-border patient referral system? - Lisa Kawatsu; Akihiro Ohkado; Kazuhiro Uchimura; Kiyohiko Izumi (BMC, 2018)
Abstract Background Tuberculosis (TB) patients crossing borders pose a serious challenge to global TB control efforts. The objectives of our study were firstly, to evaluate the trend and size of foreign-born pulmonary TB patients, who had been notified and initiated treatment in Japan but have transferred out of the country while still on treatment; and secondly, to conduct a detailed analysis of these patients and identify possible risk factors for international transfer-out, and discuss policy implications for a cross-border patient referral system for foreign-born TB patients in Japan. Methods We conducted a cross-sectional study whereby aggregated cohort data of pulmonary TB cases newly notified to the Japan TB Surveillance system between 1 January 2011 and 31 December 2015 were analyzed. Multinomial logistic regression analysis was conducted to identify and compare the risk factors for international transfer-out. Results Among the 668 foreign-born patients whose treatment outcome had been evaluated as "transferred- out", 51.3% has in fact moved to outside Japan between 2011 and 2015. The proportion of such international transfer-out of total foreign-born patients who had transferred out has more than doubled during the study period, from 23.3% in 2011 to 57.7% in 2015. Some of the risk factors for international transfer-out were being a full-time worker (Relative risk [RR] 2.86, 95% confidence interval [CI] 2.04, 3.99), being diagnosed within 0 to 2 years of arriving to Japan (RR 8.78, 95% CI 4.30,17.90) and within 3 to 5 years (RR 7.53, 95% CI 3.61, 15.68), sputum smear positive (RR 1.95, 95% CI 1.53, 2.48), and coming from Indonesia (RR 1.86, 95% CI 1.13, 3.03). Conclusions Providing continuity of care for mobile population is one of the keys to achieving the WHO's End TB Strategy targets for 2030, and results of our study indicate that a cross-border referral system should be an integral part of TB control among foreign-born persons in Japan.